The effect of employing the riglioth model on the achievement of the students of the Institute of Fine Arts in the subject of appreciation and art criticism (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the effect of employing the Reglioth model on the achievement of the students of the Institute of Fine Arts in the subject of appreciation and art criticism. Diyala Governorate, the academic year 2013-2014, and the Recluth model and the artistic appreciation subject taught to second-grade students. The research community consisted of (49) students distributed over two academic classes (first, second), (20) students were selected as a main research sample. The experimental approach with two groups (T, Z). The number of students in the experimental group was (10) students, and the number of students in the control group was (10) students. An educational program was built according to the Recluth model of taste